Pemanfaatan Temulawak (Curcuma xanthorrhiza) Sebagai Obat Cantengan Tradisional di Desa Kiara Payung, Banten - Zulfiani, Rizka; Dahlia, Siti; Sari, Widya Elfina; Fitriana, Desi Eka Nur (Universitas Medan Area, 2025)
Paronychia is an infection that occurs around the nails, causing pain, swelling, and inflammation, which can disrupt daily activities. This study aims to explore the utilization of Curcuma xanthorrhiza (temulawak) as a traditional remedy for paronychia in Kiara Payung Village. The focus of the study is on understanding the preparation, usage, and effectiveness of temulawak-based remedies used by the local community to treat paronychia. This study uses a qualitative descriptive method through semi-structured interveiews with two informants: a traditional healer and a patient who successfully recovered after using the temulawak remedy. Data analysis was conducted descriptively to illustrate the potential of the remedy. The study concludes that the remedy made from temulawak, red onion, and letik oil effectively treats paronychia after 2–3 applications. The people of Kiara Payung Village prefer traditional medicine because it is considered safe, natural, and free of side effects. This research provides evidence that temulawak remedies have significant potential as an effective alternative treatment for paronychia in Kiara Payung Village.